Expert System of Detection Defisiensi Imun Uses K-Nearest Neighbor Method - Puji Sari Ramadhan; Tugiono Tugiono; Saiful Nurarif (The IJICS (International Journal of Informatics and Computer Science), 2019)
Immune deficiency is a collection of various diseases which, due to having one or more immune system abnormalities and impairing the functioning of the immune system that are decreasing or not functioning properly, with this condition the susceptibility to infection increases. This disease is mostly suffered by children, this is because the immune system changes in children who have not been able to deal with immune attenuation attacks. For now the number of children who do not get early treatment properly, this is due to a lack of public knowledge about this skin inflammatory disease. Looking at the problems that have been raised, it is necessary to build an Expert System that is able to move expert knowledge into a system of consultation services to detect Immunodeficiency Disease based on clinical symptoms experienced by applying the K-Nearest Neighbor method which functions to process knowledge so that can conclude disease probabilities that refer to the state of the previous diagnosis to be used as an initial diagnostic analysis